Advanced Nanoprobe Strategies for Imaging Macrophage Polarization in Cancer Immunology - Junjie Zhang; Kaiyuan Tang; Yongbin Yang; Dongliang Yang; Wenpei Fan (Research)
Macrophages are ubiquitous within the human body and serve pivotal roles in immune surveillance, inflammation, and tissue homeostasis. Phenotypic plasticity is a hallmark of macrophages, allowing their polarization into distinct phenotypes M1 (pro-inflammatory, anti-tumor) and M2 (anti-inflammatory, pro-tumor) in response to local microenvironmental cues. In tumor tissues, the polarization of tumor-associated macrophages profoundly shapes the tumor microenvironment, influencing tumor progression, immune evasion, and metastasis. Therefore, the ability to image and monitor macrophage polarization is essential for comprehending tumor biology and optimizing therapeutic strategies. With the rapid advancement of nanomedicine, a diverse array of nanoprobes has been engineered to specifically target tumor-associated macrophages, offering new avenues for noninvasive in vivo imaging and real-time monitoring of macrophage dynamics within the tumor microenvironment. This perspective highlights recent advancements in macrophage-targeting nanoprobes for imaging macrophage polarization both in vitro and in vivo. It also addresses the current challenges in the field, such as enhancing probe sensitivity, specificity, and biocompatibility, while outlining the future directions for the development of next-generation nanoprobes aimed at precision oncology.